2022
DOI: 10.14198/obets2022.17.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Sistematización conceptual de las mediciones de ajuste ideológico entre la oferta de representación política y la demanda ciudadana

Abstract: Este artículo se centra en mejorar el conocimiento de las claves explicativas que relacionen la demanda de representación política de la ciudadanía, la identificación ideológica y la capacidad de los partidos de responder a dicha demanda de representación. Se plantea una propuesta de conceptualización que mida el grado de ajuste entre dichos conceptos. Se aplican tres estrategias de medición, la operativización topológica, la operativización mediante etiquetado ideológico y la medición de posicionamiento ante … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
(81 reference statements)
0
2
0
1
Order By: Relevance
“…Alaminos -Fernández, Antonio Francisco;Francés García, Francisco;Santacreu-Fernández, Óscar (2024). The explanatory order that the variables political identification, political efficacy and voter turnout have in the political system is often multidirectional.…”
Section: Citationmentioning
confidence: 99%
See 2 more Smart Citations
“…Alaminos -Fernández, Antonio Francisco;Francés García, Francisco;Santacreu-Fernández, Óscar (2024). The explanatory order that the variables political identification, political efficacy and voter turnout have in the political system is often multidirectional.…”
Section: Citationmentioning
confidence: 99%
“…This in no way means that electoral behaviour can be explained solely through party identification. The problems of dealing with dual notion of representation-identity are therefore not only confined to the conceptual level, but also extend to the methodological sphere (Calle, Martínez and Orriols, 2010;Otero, 2014;Francés et al, 2022). But while acknowledging the many challenges in measuring and formulating divergent hypotheses, most research evidence has suggested that supporters of a particular party consider that it is the party's political position that governs how they assess policy, voting behaviour and even political values (Chen and Goren, 2016;Carsey and Layman, 2006).…”
Section: Political Efficacy and Party Identity As Mediating Variables...mentioning
confidence: 99%
See 1 more Smart Citation